Efek Mediasi Variabel Work Engagement dalam Pengaruh Job Resourcefulness terhadap Individual Crafting dan Collaborative Crafting - Yahdi Ariski; Dwiarko Nugrohoseno (Jurnal Ilmu Manajemen, 2021)
This study examines the influence of job resourcefulness on individual crafting and collaborative crafting through work engagement as a mediator variable. This research uses a quantitative approach, using a survey to collect data. The sample in this study amounted to 100 employees from 4-star hotels throughout Surabaya who are registered in the Traveloka. This research used Structural Equation Model (SEM) with the assistance of Smart PLS 3.0 software as the statistical analysis. This research shows that job resourcefulness has a significant positive direct influence on individual crafting and has a significant and positive individual influence on individual crafting through work engagement on 4-star hotel employees. Job resourcefulness is found to have a significant and negative direct influence on collaborative crafting. Job resourcefulness has a significantly direct indirect influence on collaborative crafting through work engagement with 4-star hotel employees. The implications of this study need to increase the collaborative crafting employees by involving all employees in the procurement of discussion forums, so they can harmonize the thought between employees in the company so that the existence of the forum there will be similarities of perceptions so that work collaboration can be well established.